2005
DOI: 10.1002/nau.20125
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning stimulus can influence an external urethral sphincter contraction evoked by a magnetic stimulation

Abstract: A conditional sensory pudendal stimulation seems to have the capacity to inhibit the external urethral sphincter contraction induced by a magnetic stimulation. The inhibitory effect seems to depend on the latency between the peripheral and lumbosacral stimulation as well as on the degree of BLA filling. It remains to be proved if the neuromodulative effect of the conditional stimulus occurs at a spinal or supraspinal level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
3
2
Order By: Relevance
“…Currently, SMS causes a significant increase in bladder capacity, which could be due to acute activation of the inhibitory reflex pathway to the detrusor induced by stimulation of pudendal afferents. Furthermore, recent studies have shown that SMS stimulates mainly sensory afferent fibers and the urethral responses are reflexively mediated . However, in this study duloxetine, which works at the level of Onuf's nucleus, did not change amplitudes of pressure spikes in response to SMS, suggesting that the pressure spikes were unlikely to be reflex urethral responses via the afferent pathways.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Currently, SMS causes a significant increase in bladder capacity, which could be due to acute activation of the inhibitory reflex pathway to the detrusor induced by stimulation of pudendal afferents. Furthermore, recent studies have shown that SMS stimulates mainly sensory afferent fibers and the urethral responses are reflexively mediated . However, in this study duloxetine, which works at the level of Onuf's nucleus, did not change amplitudes of pressure spikes in response to SMS, suggesting that the pressure spikes were unlikely to be reflex urethral responses via the afferent pathways.…”
Section: Discussioncontrasting
confidence: 77%
“…Furthermore, recent studies have shown that SMS stimulates mainly sensory afferent fibers and the urethral responses are reflexively mediated. 6,18,19 However, in this study duloxetine, which works at the level of Onuf's nucleus, did not change amplitudes of pressure spikes in response to SMS, suggesting that the pressure spikes were unlikely to be reflex urethral responses via the afferent pathways. It is, thus, conceivable that SMS conducted in this study may be direct stimulation of only efferent fibers to external urethral sphincter.…”
Section: Discussioncontrasting
confidence: 64%
“…In relation to lower urinary tract dysfunction, underactivity of SUSRIC may be involved in bladder-sphincter dyssynergia and retentive urinary dysfunction such as Fowler's syndrome (16), while overactivity of SUSRIC may be involved in the pathophysiology of stress urinary incontinence. A possible clinical correlation of SUSRIC activation may be the elegant demonstration in men that conditioning stimuli applied to the dorsal nerve of the penis (i.e., PudN afferent fibers) inhibited URS contractions reflexively evoked by magnetic stimulation of the spinal cord applied at intervals of 20 -100 ms after the conditioning stimuli (31). Further examination of SUSRIC to characterize its physiological and pathological roles may provide another site for pharmacological therapy aimed at voiding dysfunctions.…”
Section: Discussionmentioning
confidence: 98%
“…In healthy subjects invasive cystometry has also been tested with contraction of the external urethral sphincter measured using a two‐channel microtip pressure transducer catheter in the rectum and urethra 93. Non‐invasive diagnostic tools used in early clinical trials are measurement of: (a) bladder capacity with ultrasound; (b) maximum flow rate with uroflowmetry; (c) post‐voided residual; (d) voiding efficiency; and (e) urethral opening and closing pressures and elastance in women using urethral pressure reflectometry (UPR) that demonstrates greater sensitivity and less variability that conventional urethral pressure profile approaches 94–96.…”
Section: Underactive Bladder: Potential Biomarkers Treatments and Tmentioning
confidence: 99%